Synthesis and evaluation of radiolabeled porphyrin derivatives for cancer diagnoses and their nonradioactive counterparts for photodynamic therapy. Issue 12 (29th September 2022) - Ramzi, Nur Izni; Mishiro, Kenji; Munekane, Masayuki; Fuchigami, Takeshi; Hu, Xiaojun; Jastrząb, Renata; Kitamura, Yoji; Kinuya, Seigo; Ogawa, Kazuma
Abstract : The prepared radiolabeled porphyrin derivatives showed high accumulation in tumor tissues and good phototoxicities indicating their potential for cancer theranostics. Abstract : Radioiodinated porphyrin derivatives and the corresponding nonradioactive iodine introduced compounds, [ 125 I]I-TPPOH ([ 125 I]3 ), [ 125 I]I-l -tyrosine–TPP ([ 125 I]9 ), I-TPPOH (3 ), and I-l -tyrosine–TPP (9 ) were designed, synthesized, and evaluated by in vitro and in vivo experiments. In cytotoxicity assays, 3 and 9 exhibited significant cytotoxicity under light conditions but did not show significant cytotoxicity without light irradiation. Biodistribution experiments with [ 125 I]3 and [ 125 I]9 showed similar distribution patterns with high retention in tumors. In photodynamic therapeutic (PDT) experiments, 3 and 9 at a dose of 13.6 μmol kg −1 weight with 50 W single light irradiation onto the tumor area significantly inhibited tumor growth. These results indicate that the iodinated porphyrin derivatives [ 123/nat I]3 and [ 123/nat I]9 are promising cancer theranostic agents.